Influence of alcohol consumption on risky behaviors among students of first and fourth year of the Medical Faculty - Książek, Piotr; Dreher, Piotr; Grabska, Kinga; Trojanowska, Dominika; Słowińska, Agata; Dreher, Sylwia (Polish Journal of Public Health, 2016)
Introduction. The problem university students’ drinking in Poland has evoked greater interest lately. Numerous studies conducted in the recent years have indicated an increase in consumption of high-proof alcoholic beverages among students. Aim. The aim of the study was to explore the influence of alcohol over on risky behavior among first and fourth year students of the Medical Faculty at the Medical University in Lublin during the academic year 2011/2012. Material and methods. The study looked at 120 students, 45 men and 75 women; 60 people from the first and 60 people from the fourth year of the Medical Faculty. The method of an author’s original questionnaire, which was fully anonymous, was used. Answering 22 questions included in the questionnaire was voluntary, those completing the questionnaires could refuse to participate in the study at any time. Results. Statistically significant correlations between students who abused alcohol and their risky behaviors were found. Conclusions. There are some negative consequences of young people’s drinking alcohol and the most frequent symptoms They include: driving under the influence, engaging in risky sexual behaviors or starting fights. Several respondents admitted that they were passengers while the driver was intoxicated. Students being in a state of intoxication more often engaged in sexual activities. Alcohol consumption might also result in irrational decisions which could endanger health and lives e.g.: jumping from a roof. A few students of the fourth year were occasionally involved in gambling. A number of students admitted undergoing medical assistance after alcohol consumption.